REPORTING OF TESTAMENTARY DEEDS FOR INDONESIAN CITIZENS ABROAD - Salsabila, Nadia (JILPR Journal Indonesia Law and Policy Review, 2025)
This article will discuss the inconsistency of will reporting arrangements for Indonesian citizens abroad. The purpose of this research is to review and analyze the synchronization of Article 11 paragraph (1) of the Regulation of the Minister of Law and Human Rights Number 60 of 2016 with Article 8 letter c of the Regulation of the Minister of Foreign Affairs Number 5 of 2018 and to review and analyze the roles and responsibilities of Notaries in reporting testamentary deeds for Indonesian citizens abroad. By using normative juridical research, this research is prescriptive and uses the type of research on the level of vertical and horizontal synchronization. The approaches used by the author are statute approach and conceptual approach. Results of the research, First : The synchronization of the provisions of reporting the will deed for Indonesian citizens abroad is carried out by seeing that the position of Article 8 letter c of the Minister of Foreign Affairs Regulation Number 5 of 2018 is a specificity of Article 11 paragraph (1) of the Minister of Law and Human Rights Regulation Number 60 of 2016. Second: Notaries only have responsibility for the deeds they make or that are presented to them. Therefore, the Notary does not have a direct obligation and responsibility to report on testamentary deeds made by Indonesian citizens abroad.